The p27 Pathway Modulates the Regulation of Skeletal Growth and Osteoblastic Bone Formation by Parathyroid Hormone–Related Peptide. (30th June 2015) - Zhu, Min; Zhang, Jing; Dong, Zhan; Zhang, Ying; Wang, Rong; Karaplis, Andrew; Goltzman, David; Miao, Dengshun
ABSTRACT Parathyroid hormone–related peptide (PTHrP) 1–84 knock‐in mice (Pthrp KI) develop skeletal growth retardation and defective osteoblastic bone formation. To further examine the mechanisms underlying this phenotype, microarray analyses of differential gene expression profiles were performed in long bone extracts from Pthrp KI mice and their wild‐type (WT) littermates. We found that the expression levels of p27, p16, and p53 were significantly upregulated in Pthrp KI mice relative to WT littermates. To determine whether p27 was involved in the regulation by PTHrP of skeletal growth and development in vivo, we generated compound mutant mice, which were homozygous for both p27 deletion and the Pthrp KI mutation (p27‐/‐Pthrp KI). We then compared p27‐/‐Pthrp KI mice with p27‐/‐, Pthrp KI, and WT littermates. Deletion of p27 in Pthrp KI mice resulted in a longer lifespan, increased body weight, and improvement in skeletal growth. At 2 weeks of age, skeletal parameters, including length of long bones, size of epiphyses, numbers of proliferating cell nuclear antigen (PCNA)‐positive chondrocytes, bone mineral density, trabecular bone volume, osteoblast numbers, and alkaline phosphatase (ALP)‐, type I collagen‐, and osteocalcin‐positive bone areas were increased in p27‐/‐ mice and reduced in both Pthrp KI and p27‐/‐Pthrp KI mice compared with WT mice; however, these parameters were increased in p27‐/‐Pthrp KI mice compared with Pthrp KI mice. As well, protein expression levels of PTHR, IGF‐1, and Bmi‐1, and the numbers of total colony‐forming unit fibroblastic (CFU‐f) and ALP‐positive CFU‐f were similarly increased in p27‐/‐Pthrp KI mice compared with Pthrp KI mice. Our results demonstrate that deletion of p27 in Pthrp KI mice can partially rescue defects in skeletal growth and osteoblastic bone formation by enhancing endochondral bone formation and osteogenesis. These studies, therefore, indicate that the p27 pathway may function downstream in the action of PTHrP to regulate skeletal growth and development. © 2015 American Society for Bone and Mineral Research.